KEBERADAAN PEMEGANG SAHAM DALAM RUPS DENGAN SISTEM TELECONFERENCE TERKAIT JARINGAN BERMASALAH DALAM PERSPEKTIF CYBER LAW - Ni Ketut Supasti Dharmawan (University of Udayana, 2015)
In Indonesia, the General meeting of Shareholder through teleconference mechanism can be conducted under the provision of Article 77 of Law No. 40 of 2007 concerning Limited Liability Company. This teleconferencing mechanism allows all participants to see and to hear each other as well as to participate in the teleconference meeting. There is legal vacuum with regard to position of shareholders in the General Meeting by teleconference mechanism, especially in the case of network problems. However, by analogy with the legal construct of the provisions of Article 90 of the Company Law can be stated that the position of shareholders continues to be recognized as a legal subject who has legal right and has valid votes counted even if the minutes of the meeting have not been signed electronically because internet network problem as long as treatise or the minute of General Meeting of shareholders is made by notarial deed and shall be signed by the Notary who made the deed.